Eigenspannungsanalyse an Schichtverbunden mittels inkrementeller Bohrlochmethode - Held, Esther (KIT Scientific Publishing, 2021)
The incremental hole drilling method is used and further developed to determine residual stress states in thick film systems. The application limits regarding the applicability on film systems and the influence of the system's built up is examined by finite element simulations. A new evaluation method for the hole drilling method is proposed. Using this method residual stress states in thick film systems can be determined reliably in the coating, at the interface and also in the substrate.